Confessional identity of Orthodox Ukrainians in the conditions of modern calls - Boreyko, Yuri (Skhid, 2016)
The problems related to confessional identity of Orthodox Ukrainians in the conditions of modern calls are analysed in the article. Religious identification is a major mechanism of socialization and education of personality, that appears in realization by it own group belonging. The result of process of identification is an identity that is formed in intercommunication with confessional belonging. Connection of religious and ethnic identity is historically the inherent line of religious situation in Ukrainian society, where traditionally there was correlation between religious and ethnic belonging. Influence of ethnic descriptions unavoidable affects existence of religion, leads to forming of her certain features peculiar only to this ethnos. A confessional identity actualized in the conditions when a religious identity envisages the concrete form of religiousness. Belonging to Orthodoxy appears the meaningful, valued painted marker of identification. Meaningfulness of confessional belonging grows in the conditions of deformation of social structures and institutes. In a situation with the Ukrainian Orthodox identity it is about the diffuse, vague identity, when an individual did not yet do a responsible world view choice, that is why image of his I characterized by fuzziness and vagueness. As a sign of confession is not acquires functions of basic identification, the nature of beliefs are mostly personal, when confessional identification is rather arbitrary. Self-declaration of identification with Orthodox confession largely has nominal character, predefined by perception of Orthodoxy as cultural tradition, and confessional belonging - as a contribution to this tradition. Self-identification with Orthodox confession is related to purposeful efforts of religious associations, and also with the process of equation of national and confessional self-identification. Belonging to Orthodox confession has symbolic character, demonstrates involvement of believing individual to the dominant ethnic and religious association.